Public administration and the life science: revisiting biopolitics - Meyer-Emerick, Nancy (2007)
Biopolitics applies methodology from the life sciences to study human behavior and policy related to living things. Although Gulick introduced the concept to public administration more than 25 years ago. It remains nearly absent in the public administration literature. This article reintroduces the origin, concepts, and methodology of biopolitics and explores its application to public administration but also suggests that a public administration perspective would be a valuable contribution in return. - Reproduced.
Keywords: Public policy; Public administration